¿Son los tapones auditivos eficaces para prevenir los efectos de la contaminación auditiva mediante la atenuación sonora? - Coello, Fausto (2017)
Context: the effects of exposure to noise pollution include auditory symptoms: hearing loss, elevation of the auditory threshold, acoustic trauma and also non-auditory psychological, physical and social.Material and methods: a descriptive, analytical, cross-sectional study, the efficacy of the sound attenuation of the personalized hearing protectors was determined in a group of 33 male patients without physical alterations in the external auditory canal, by means of the comparison of the responses obtained in the ear Real-Ear Unaided Response, and with the ear sealed by means of a custom-made silicone plug (Real-Ear Occluded), in the presence of stable external broadband noise of 65 dB Of intensity, using a precision equipment certified with ISO standards, the Verifit of Audioscan. Results: it was found that there is a greater protection to high decibels with frequencies 2000 Hz, 3000 Hz and 4000 Hz, falling from 65 to 40 decibels, which means a reduction of 61%, there is no significant difference between both ears, Which is explained by the particularities in the anatomical forms, depth of insertion and the proper placement of the microphone probe. The average bilateral attenuation values in dB SPL that is achieved in the different frequencies with personalized ear protection plugs vary depending on the same, with 250 Hz being 9.97 in the right ear and 9.36 in the left ear and with 6000 Hz 15.28 in the right ear and 13.64 in the left ear. Greater attenuation was found with 3000 Hz (OD: 32.11 OI: 30.69), 2000 Hz (OD: 28.33 OI: 28.47) and 4000Hz (OD: 27.28 OI: 26.67).Conclusion: the use of hearing protectors; Achieves an evident reduction of the sound levels, especially with acute frequencies, which are the first ones whose thresholds are affected when undergoing high levels of noise for prolonged times